A real-life illusion of assimilation in the human face: eye size illusion caused by eyebrows and eye shadow - Morikawa, Kazunori; Matsushita, Soyogu; Tomita, Akitoshi; Yamanami, Haruna (Frontiers in Human Neuroscience, 2015)
Does an assimilative illusion like the Delboeuf illusion occur in the human face? We investigated factors that might influence the perceived size of the eyes in a realistic face. Experiment 1 manipulated the position of the eyebrows (high or low), the presence/absence of eye shadow, and the viewing distance (0.6 m or 5 m), then measured the perceived eye size using a psychophysical method. The results showed that low eyebrows (i.e., closer to the eyes) make the eyes appear larger, suggesting that the assimilation of eyes into the eyebrows is stronger when the eye-eyebrow distance is shorter. The results also demonstrated that the application of eye shadow also makes the eyes look larger. Moreover, the effect of eye shadow is more pronounced when viewed from a distance. In order to investigate the mechanism of the eye size illusion demonstrated in Experiment 1, Experiment 2 measured the magnitude of the Delboeuf illusion at a viewing distance of 0.6 m or 5 m, with or without gray gradation simulating the eye shadow that was used in Experiment 1. The experiment demonstrated that the Delboeuf illusion is modulated by viewing distance and gradation in the same way as the eye size illusion. These results suggest that the eye size illusion induced by the eyebrows and the Delboeuf illusion involve the same mechanism, and that eye shadow causes the assimilation of the eyes into itself and enhances assimilation between the eyes and the eyebrows.